2023
DOI: 10.5829/ijee.2023.14.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Improving Energy Efficiency in Agronomical Systems

Abstract: Increasing demand for agricultural products and production of resource constraints-especially the limitation of cultivable areas -have made the highest yield per unit area the main goal of agricultural producers. Agriculture is a system exhibiting high energy consumption and production. Since energy has a direct impact on the efficiency of crop production, a sustainable agricultural system needs to be analyzed in terms of its input and output energy to determine the total consumed energy of production per unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…used in planting of watermelon (kW) HLI= EQHL. HL [6] in which HLI is energy consumed by human in terms of MJ.ha -1 , EQHL is human energy equivalent in terms of MJ.h -1 and HL is the time of human labor in terms of ha -1 . The efficiency of watermelon planting system was measured by three indexes according to the following equations (3):…”
Section: Pi= Eqp P [2]mentioning
confidence: 99%
See 1 more Smart Citation
“…used in planting of watermelon (kW) HLI= EQHL. HL [6] in which HLI is energy consumed by human in terms of MJ.ha -1 , EQHL is human energy equivalent in terms of MJ.h -1 and HL is the time of human labor in terms of ha -1 . The efficiency of watermelon planting system was measured by three indexes according to the following equations (3):…”
Section: Pi= Eqp P [2]mentioning
confidence: 99%
“…Due to the limitation of energy supply sources, the necessity of optimal use of energy has been revealed. However, research has shown that the higher productivity of agricultural ecosystems has only been accompanied by the help and increase in energy consumption in various production sectors, such as seeds, pesticides, chemical fertilizers, and fuel (5,6). In fact, the lack of optimal use of energy in agriculture in developing countries has created major limitations for the production of agricultural products, and thus, the realization of sustainable agriculture (7).…”
Section: Introductionmentioning
confidence: 99%